Respuesta :

Answer:

y = 2

Step-by-step explanation:

Given

[tex]\frac{1}{3}[/tex](y + 7) = 3(y - 1)

Multiply both sides by 3 to clear the fraction

y + 7 = 9(y - 1) ← distribute

y + 7 = 9y - 9 ( subtract 9y from both sides )

- 8y + 7 = - 9 ( subtract 7 from both sides )

- 8y = - 16 ( divide both sides by - 8 )

y = 2

Answer:

y = 2

Step-by-step explanation:

[tex]\frac{1}{3} y+\frac{7}{3} =3y-3[/tex]

[tex]\frac{1}{3}y+\frac{7}{3}-\frac{7}{3}=3y-3-\frac{7}{3}[/tex]

[tex]\frac{1}{3} y=3y-\frac{16}{3}[/tex]

[tex]-\frac{8}{3}y=-\frac{16}{3}[/tex]

- 8y = - 16

y = 2

ACCESS MORE